2015
DOI: 10.1021/acssuschemeng.5b00619
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible Deep Eutectic Solvents Based on Choline Chloride: Characterization and Application to the Extraction of Rutin from Sophora japonica

Abstract: The development of novel green solvents has been one of the hottest subjects in green chemistry. Deep eutectic solvents (DESs) have logically and naturally emerged in the search for more biocompatible and biodegradable solvents. In this study, some basic physical properties, including viscosity, conductivity and density, of twenty DESs prepared from choline chloride and various hydrogen bond donors were investigated systematically. In addition, the biocompatibility of the tested DESs was qualitatively and quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
269
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 479 publications
(299 citation statements)
references
References 57 publications
10
269
0
3
Order By: Relevance
“…According to the data available in the literature, viscosities and/or densities for the investigated DESs are as follows: ChCl : fructose [12]. Addition of 25% and 50% of water significantly improved rutin extraction in all experiments, which could be attributed to the decrease in the viscosity of the DESs by addition of water, as described by Duan et al [6] and Zhao et al [11]. When rutin extraction yields are compared, there is no significant difference among the experiments performed with addition of 50% and 25% of water with the same DES, and, as indicated in Figure 1, there is no need to perform the extraction for 3 or 6 h.…”
Section: Selection Of the Best Des For Rutin Extractionmentioning
confidence: 53%
See 1 more Smart Citation
“…According to the data available in the literature, viscosities and/or densities for the investigated DESs are as follows: ChCl : fructose [12]. Addition of 25% and 50% of water significantly improved rutin extraction in all experiments, which could be attributed to the decrease in the viscosity of the DESs by addition of water, as described by Duan et al [6] and Zhao et al [11]. When rutin extraction yields are compared, there is no significant difference among the experiments performed with addition of 50% and 25% of water with the same DES, and, as indicated in Figure 1, there is no need to perform the extraction for 3 or 6 h.…”
Section: Selection Of the Best Des For Rutin Extractionmentioning
confidence: 53%
“…All DESs were prepared as described in the previous literature [11]. Choline chloride (ChCl) as HBA was mixed with HBD in a certain ratio as stated in Figure 1.…”
Section: Preparation Of Dessmentioning
confidence: 99%
“…Racemic PED and SO were purchased from Guangzhou Qiyun bioscience Co. Ltd. All other reagents used to synthesize DESs were of analytical grade and were from commercial sources. The preparation of DESs was referenced by previous literature (Zhao et al 2015). Briefly, choline chloride and hydrogen bond donor were mixed at a fixed molar ratio at 80 °C for appropriately 2 h until the formation of a stable homogeneous liquid.…”
Section: Methodsmentioning
confidence: 99%
“…quaternary ammonium salts are readily available. 4 Design for degradation Most of the components of DES are biodegradable [31] and as such do not persist in the environment for a longer period of time. For example, cholinium alkanoates based DESs are environmentally benign and biodegradable [32,33].…”
Section: Less Hazardous Constituents and Productsmentioning
confidence: 99%
“…Zhao et al, [31] investigated the extraction of flavonoid from the flower buds of Sophora japonica using several choline based deep eutectic solvents. It was found that eutectic solvents based on choline/triethylene glycol can be efficiently used as a potential green solvent for the removal of rutin in sophora japonica with an extraction efficiency of 194.17 ±2.31 mg.g -1…”
Section: Deep Eutectic Solvent As a Novel Benign Extractant For Bioacmentioning
confidence: 99%